The relative lethal toxicity of pharmaceutical and illicit substances: A 16‐year study of the Greater Newcastle Hunter Area, Australia. Issue 9 (17th July 2019) - Brett, Jonathan; Wylie, Claire E.; Raubenheimer, Jacques; Isbister, Geoff K.; Buckley, Nick A.
Abstract : Aims: We aim to calculate 2 metrics of relative lethal toxicity; the fatal toxicity index (FTI; number of deaths per year of a daily dose) and the case fatality (CF; number of deaths per overdose) with a focus on opioids, antidepressants, antipsychotics, benzodiazepines and illicit drugs. Methods: This descriptive cohort study used the Australian National Coronial Information System (NCIS) to identify a population of individuals with drug‐associated deaths in the Greater Newcastle Hunter Area between January 2002 and December 2016. This was combined with Australian medicine dispensing data and corresponding data from the Hunter Area Toxicology Service to calculate FTI and CF. Results: There were 444 drug‐related deaths and 21, 296 overdoses during the study period. FTI and CF were well correlated (Spearman's rho 0.64, P < .001). Of the classes of interest, opioids had the highest FTI (40.3 95% confidence interval [CI] 35.2–45.4 deaths per 100 years of use at the defined daily dose or deaths/DDD/100 years) and CF (12.4% 95%CI 11.0–13.9). Fentanyl, methadone and morphine had the highest relative fatal toxicity within this class. Tricyclic antidepressants had the highest relative fatal toxicity of all antidepressants (FTI 14.5 95%CI 9.7–19.3 deaths/DDD/100 years and CF 7.1% [95%CI 4.8–9.3]) and benzodiazepines appeared to be more associated with multiple agent deaths than single. Of the illicit drugs, heroin had the highest CF (26.4%, 95%CI 19.1–33.7). Conclusion: Knowledge of relative lethal toxicity is useful to prescribers and medicines and public health policy makers in restricting access to more toxic drugs and may also assist coroners in determining cause of death.